Oil painting on tinplate by Francisco José Resende - Ana Rita Veiga (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article focuses on the study of execution techniques, material composition and condition of three oil paintings on tinplate – a thin sheet of steel coated with tin - by the Portuguese painter Francisco José Resende (1825-1893). Although the choice to paint on a metallic support was not very common in the nineteenth century, the painter executed several works on this support. The comparative results focus on Francisco Resende’s technique of execution, the materials used in the paint layers and on the support of the three works which are being studied. Although executed in the same period, they show different conservation problems - namely delamination and blistering of the paint layers, and also corrosion of the support.